2016
DOI: 10.1016/j.chb.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Can machines talk? Comparison of Eliza with modern dialogue systems

Abstract: To find if current dialogue systems use the same, psychotherapist questioning technique as JosephPre-publication version.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(42 citation statements)
references
References 20 publications
0
38
0
4
Order By: Relevance
“…Despite these issues, both early (Weizenbaum, 1966) and very recent (Hasler, Tuchman, & Friedman, 2013;Hill, Ford, & Farreras, 2015) research with text-based Human-Chatbot interactions have consistently pointed to their potential benefits, particularly with regard to the motivation they seem to inspire in their users. Furthermore, research seeking to build directly on Weizenbaum' original efforts has suggested that current Chatbots have and continue to improve as many of them learn from their "roundthe-clock" web-based interaction with interested humans from around the globe (Shah, Warwick, Vallverdú, & Wu, 2016).…”
Section: Technology For Enhancing Interest and Learningmentioning
confidence: 99%
“…Despite these issues, both early (Weizenbaum, 1966) and very recent (Hasler, Tuchman, & Friedman, 2013;Hill, Ford, & Farreras, 2015) research with text-based Human-Chatbot interactions have consistently pointed to their potential benefits, particularly with regard to the motivation they seem to inspire in their users. Furthermore, research seeking to build directly on Weizenbaum' original efforts has suggested that current Chatbots have and continue to improve as many of them learn from their "roundthe-clock" web-based interaction with interested humans from around the globe (Shah, Warwick, Vallverdú, & Wu, 2016).…”
Section: Technology For Enhancing Interest and Learningmentioning
confidence: 99%
“…This particular finding appears unique compared to other text-based interventions described in the literature but is consistent with NICH program emphases on building rapport and the importance of the human element in behavior change. In stark contrast with continued attempts to automate interventions, 21 the NICH program's text-messaging component remains truly personalized. This unique component, although more time consuming than automated delivery systems, may allow interventionists the needed flexibility to tailor text content to individual patient and family characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Chatbot applications have been around for a long time; the first well-known chatbot is Joseph Weizenbaum"s Eliza program developed in the early 1960s. Eliza facilitated the interaction between human and machine through a simple pattern matching and a template-based response mechanism to emulate the conversation [6,7].…”
Section: A Chatbots Applications and Usesmentioning
confidence: 99%